Neoliberalism and four spheres of authority in American education: Business, class, stratification, and intimations of marketization. Issue 2 (February 2020) - Ford, Brian
This is the second of three articles on "Sources of Authority in Education". All use the work of Amy Gutmann as a heuristic device to describe and explain the prevalence of market-based models of Education Reform in the United States as part of what Pasi Sahlberg terms the Global Education Reform Movement (GERM). This movement is based on neoliberal tenets and encourages the enterance of private business and the adoption of business practices and challenges long standing notions of democratic education. The first article is "Negating Amy Gutmann: Deliberative Democracy, Education and Business Influence" (to be published in Democracy and Education ) and the third is "The Odd Malaise of Democratic Education and the Inordinate Influence of Business" (to be published in Policy Futures in Education ). My intent is to include them, along with a fourth article, "Profit, Innovation and the Cult of the Entrepreneur: Civics and Economic Citizenship, " as chapters of a proposed volume, Democratic Education and Markets: Segmentation, Privatization and Sources of Authority in Education Reform. The "Negating Amy" article looks primarily at Deliberative Democracy. The present article considers the promise of Egalitarian Democracy and how figures such as Horace Mann, John Dewey, and Gutmann have argued it is based largely on the promise of public education. "The Odd Malaise" article begins by offering some historical background, from the origins of the common school in the 1600s to market emulation models, No Child Left Behind and how this is reflected in a "21st century schools" discourse; it ends by considering and underlying theme: what happens to the Philosophy of Education when Democracy and Capitalism are at odds. The "Profit, Innovation" article then looks at how ideological forces are popularized, considering Ayn Rand's influence, the concept of Merit, Schumpeter's concept of 'creative destruction, ' and the ideal of the entrepreneur as related sources in a changing common sense, pointing out that the commonplace of identifying the innovator and the entrepreneur is misplaced. The present article accordingly begins to question business influence and suggest show we may outline its major features using Amy Gutmann's work as a heuristic device to interpret business-influenced movements to reform public education. Originally the title was Turning Amy Gutmann on her Head. Consequently it returns to Gutmann's Democratic Education and its three sources of authority, suggesting that the business community is a fourth source. As such, it is in a contest to supplant the systems of deliberative democracy for which Gutmann advocates. It continues with a consideration of what might be called a partial historical materialist analysis – the growth of inequality in the United States (and other countries) since the 1970s; this correlates with much of the basis for changes in the justifications and substance of Education reform. After casting this question in principal-agent terms, it then looks at both those who sought to create a public will for public education and recent reform movements that have sought to redirect public support from a unified education system and instead advocate a patchwork of charters, vouchers for private schools, on-line education, home schooling, virtual schools and public schools based on market emulation models. Drawing from other theories of education, especially Plato (and the Spartan model), Locke, and John Stuart Mill, it also suggests that it might be instructive to compare Gutmann's three sources of authority to Abraham Kuyper's concept of Sphere sovereignty. It concludes that ultimate authority for education is —or should be—, somewhat paradoxically, vested in the adult the child will become, creating practical problems regarding the education of the sovereign that are never fully resolved and which may, in fact, be unresolvable based on rational deliberation. Finally, it looks at one instrument of business, market segmentation, and its importance as a motivating factor for education reform.